(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Fetus papyraceous is defined as a compressed fetus, mummified, parchment-like remainsof a dead twin or triplet that is retained in-utero after intrauterine death in the second trimester.We report a case of one fetus papyraceous with maternal coagulopathy and no maternaland fetal complications in the post-partum period. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 160-163